Immunoglobulin M nephropathy nephropathy in adults and adolescents in India: A single-center study of natural history - A M Singhai; A V Vanikar; K R Goplani; K V Kanodia; R D Patel; K S Suthar; H V Patel; M R Gumber; P R Shah; H L Trivedi (Wolters Kluwer Medknow Publications, 2011)
Background: Immunoglobulin M nephropathy (IgMN) is an idiopathic glomerulonephritis (GN) usually presenting clinically as steroid resistant/dependent nephrotic syndrome (NS) with pathology of mesangial proliferative GN or focal and segmental glomerulosclerosis with diffuse predominant mesangial IgM deposits. Not much information is available about its natural history. This is the first Indian study to our knowledge on IgMN in adults and adolescents. Materials and Methods: We evaluated renal biopsies performed at our center between January,'04 to September,'09. Biopsies of all adolescents and adults were evaluated for IgMN and we studied their age, gender distribution, blood pressure (BP), disease duration, steroid/immunosuppressive management and serial serum creatinine (SCr), urinary proteins, and BP values. Patients with other systemic diseases/infections and children were excluded. Results: IgMN constituted 4.3% of 2702 adult renal biopsies. No significant gender predilection was noted. Males presented at average age of 23.1 years, females at 30 years. Steroid-dependent NS was the commonest presentation noted in 75% followed by steroid-resistant NS. Hypertension was noted in 10% patients. Mesangial proliferative GN (MePGN) was commonest histopathological finding noted in 74.4%, followed by focal segmental glomerulosclerosis (FSGS) in 16.2%, and minimal change disease (MCD) in 9.4% biopsies. Sole IgM deposits were noted in 88.5%. All MCD, 35.6% MePGN reached remission, FSGS progressed to renal failure by 1 year. Hypertension, proteinuria, interstitial fibrosis, and FSGS were bad prognosticators. Conclusions: This is the first Indian study of IgMN in adults and adolescents carried out over a period of 5.8 years, which has shown that hypertension, proteinuria, and interstitial fibrosis at presentation have bad prognosis.